Gandhi my experiments with truth : an autobiography - Gandhi Mahatma 1869-1948 (Indiana Publishing House for Crossland Books, 2009)
Mohandas K. Gandhi is one of the most inspiring figures of our time. In his classic autobiography he recounts the story of his life and how he developed his concept of active nonviolent resistance, which propelled the Indian struggle for independence and countless other nonviolent struggles of the twentieth century.